Uji Aktivitas Antiinflamasi Teh Cang Salak Secara In Vitro Dengan Metode Stabilisasi Membran Human Red Blood Cell - Burhannuddin Burhannuddin; I Wayan Karta (Faculty of Pharmacy, Universitas Muslim Indonesia, 2023)
The use of natural ingredients can be an alternative as an anti-inflammatory agent with lower side effects. This study aims to determine the anti-inflammatory activity of cang salak tea in vitro using the human red blood cell membrane stabilization method. Cang salak tea is made into a drink in four formulations, namely P1, P2, P3, and P4 with a volume of 200 ml each. The four formulations were tested for phytochemicals and anti-inflammatory with red blood cell membrane stabilization method using diclofenac sodium as a positive control. The percentage value of red blood cell membrane stability for each formulation was then analyzed statistically with One-Way Anova and LSD tests to see the level of difference between formulations and their effect on cell membrane stability. The formulation of cang salak tea contains phytochemical compounds such as folinol (379,094 - 430,299 mg/100g GAE), flavonoids (5,299 - 7,959 mg/100g QE), alkaloids (24,312 - 28,472 mg/100g) and has antioxidant activity with a value of 3,996 - 6,222 ppm. The highest levels of active polyphenolic compounds were found in the P2 formulation, flavonoids in the P2 formulation, and alkaloids in the P3 formulation. The highest antioxidant activity was found in cang salak tea formulation P1 which had the lowest PPM value in the IC50 test. The percentage of red blood cell membrane stability in various formulations of cang salak tea had a significant difference with the highest value in formulation P1 (112.6 %), followed by formulation P2 (102 %), P3 (100, 2 %), and P4 (99, 7%) (P≤0.05). Based on the LSD test results of cang salak tea formulations P1, P2, and P3 were significantly different from the positive control (P≤0.05). While the P4 formulation was not significantly different from the positive control (P≥0.05). Cang salak tea formulations P1, P2, P3, and P4 were able to stabilize red blood cell membranes which showed strong anti-inflammatory activity